Cortical and Subcortical Network Dysfunction in a Female Patient With NEXMIF Encephalopathy - Cioclu, Maria Cristina; Coppola, Antonietta; Tondelli, Manuela; Vaudano, Anna Elisabetta; Giovannini, Giada; Krithika, S.; Iacomino, Michele; Zara, Federico; Sisodiya, Sanjay M.; Meletti, Stefano (Frontiers in Neurology, 2021)
The developmental and epileptic encephalopathies (DEE) are the most severe group of epilepsies. Recently, NEXMIF mutations have been shown to cause a DEE in females, characterized by myoclonic–atonic epilepsy and recurrent nonconvulsive status. Here we used advanced neuroimaging techniques in a patient with a novel NEXMIF de novo mutation presenting with recurrent absence status with eyelid myoclonia, to reveal brain structural and functional changes that can bring the clinical phenotype to alteration within specific brain networks. Indeed, the alterations found in the patient involved the visual pericalcarine cortex and the middle frontal gyrus, regions that have been demonstrated to be a core feature in epilepsy phenotypes with visual sensitivity and eyelid myoclonia with absences.